Impact of Patient Choice for Different Postcesarean Delivery Analgesic Protocols on Opioid Consumption: A Randomized Prospective Clinical Trial. Issue 1 (March 2020) - Carvalho, B.; Sutton, C.D.; Kowalczyk, J.J.; Flood, P.D.
Abstract : ( Reg Anesth Pain Med . 2019;44:578–585) Pain management after cesarean delivery is typically selected by the physician without patient input. Shared decision-making between provider and patient may improve patient care. A recent study showed patients who requested a higher intrathecal morphine dose for cesarean delivery had increased opioid requirements and greater postoperative pain, regardless of the actual dose administered. This study aimed to determine whether postoperative oxycodone requirements and pain scores could be reduced and satisfaction increased when patients were given a choice for their postcesarean delivery analgesic protocol.